Pentingnya Tablet Tambah Darah untuk Mencegah Anemia pada Remaja Putri - Fatmawati, Tina Yuli; Jeki, Andicha Gustra (Jurnal Abdimas Kesehatan (JAK), 2025)
One of the nutritional problems that is often encountered in young women is anemia. Teenage girls are prone to suffering from anemia because they lose a lot of blood during menstruation. Adolescent girls who suffer from anemia are at risk of developing anemia during pregnancy. Anemia also increases the risk of impaired learning concentration and decreased academic achievement. Considering the magnitude of this problem, one of the efforts to overcome anemia in young women is by taking the supplement Blood Increasing Tablets. The aim of this activity is to increase young women's knowledge about the importance of blood supplement tablets. This community service activity was carried out at the Al Hidayah Islamic Boarding School, Jambi City, targeting 20 young women. The method provided is through lectures, discussions and questions and answers, pre-test and post-test. The results of the activity showed that there was an increase in the knowledge of young women after being given health education about the importance of blood supplement tablets to prevent anemia. Young women are expected to always actively seek information about the importance of blood supplement tablets, and pay attention to their nutritional intake so they can avoid anemia.